Does higher longevity harm economic growth? - Sirag, Abdalla; Mohamed Nor, Norashidah; Law, Siong Hook (Association of Economists of Vojvodina, 2020)
This study contributes to economic growth literature by providing new evidence on the relationship between life expectancy and economic growth utilising the recently developed dynamic panel threshold estimator. The sample of this study contains a total of 112 developed and developing countries covering the period from 1981 to 2010. The findings indicate the existence of a non-linear relationship between life expectancy and economic growth. In particular, life expectancy is useful for economic growth but only up to a certain threshold level; any further increase in longevity above the threshold would adversely affect growth. These findings emphasise the role of demographic transition in explaining the relationship between health and economic growth.